Susceptibility of Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae) Collected from Central Java Province to Emamectin Benzoate, Chlorantraniliprole, and Spinetoram - Suryani, Julia Nanda; Trisyono, Y. Andi; Martono, Edhi (Jurnal Perlindungan Tanaman Indonesia, 2022)
Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) is a new pest on maize that has successfully spread to various regions in Indonesia. This pest can cause severe damage to the affected plants. Most farmers have relied on synthetic insecticides for control. This research was conducted to determine susceptibility level of S. frugiperda larvae to emamectin benzoate, chlorantraniliprole, and spinetoram insecticides by using the diet-dipping method. There is no registered insecticide to control S. frugiperda, so the three types of insecticides used were based on the recommendation of the Ministry of Agriculture of the Republic of Indonesia. Five field-collected population from Central Java and a laboratory populations of S. frugiperda were used to develop a baseline susceptibility for each insecticide. First instar larvae of S. frugiperda were placed in vials containing artificial diet treated with insecticides and an untreated control (treated with water only), observed for mortality on the seventh day and data was analyzed using probit. S. frugiperda from Tegowanu was the most susceptible to emamectin benzoate (LC50 = 0.11 mg/L), while the least susceptible population was from Wedi (LC50 = 0.39 mg/L) with the resistance ratio (RR) values of 0.45-folds and 1.60-folds compared to the laboratory population, respectively. S. frugiperda from Ngombol was the most susceptible population to chlorantraniliprole (LC50 = 12.63 mg/L), while the least susceptible population was from Tegowanu (LC50 = 30.29 mg/L) with RR values of 0.90- and 2.15-fold compared to the laboratory population, respectively. Meanwhile, S. frugiperda from Jogonalan was the most susceptible to spinetoram (LC50 = 2.75 mg/L), while the population from Wedi was the least susceptible (LC50 = 5.94 mg/L) with the RR values of 0.52- and 1.12-fold compared to the laboratory population. Field-collected S. frugiperda populations were still susceptible to the three tested insecticides tested and emamectin benzoate being the most toxic compared to spinetoram and chlorantraniliprole.